2015
DOI: 10.1111/tpj.13077
|View full text |Cite
|
Sign up to set email alerts
|

MYBD employed by HY5 increases anthocyanin accumulation via repression of MYBL2 in Arabidopsis

Abstract: SUMMARYPhotomorphogenesis is an essential program in plant development. This process is effected by the balanced cooperation of many factors under light and dark conditions. In a previous study, we showed that MYB hypocotyl elongation-related (MYBH) is involved in cell elongation. To expand our understanding of MYBH function, we performed a yeast two-hybrid assay and identified an MYB-like Domain transcription factor (MYBD). In this study, we investigated the function of MYBD, which is an MYBH homolog involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(60 citation statements)
references
References 63 publications
1
59
0
Order By: Relevance
“…29 Our recent study found that AtMYBD may also regulate MYBL2 expression in a diurnal manner leading to anthocyanin accumulation in the plant. 17 Taken together, our results suggest that AtMYBD may also work as a regulator of anthocyanin accumulation in a circadian-dependent manner. This speculation still requires further studies to validate it.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…29 Our recent study found that AtMYBD may also regulate MYBL2 expression in a diurnal manner leading to anthocyanin accumulation in the plant. 17 Taken together, our results suggest that AtMYBD may also work as a regulator of anthocyanin accumulation in a circadian-dependent manner. This speculation still requires further studies to validate it.…”
mentioning
confidence: 56%
“…[14][15][16] Currently, we have found that AtMYBD expression is also controlled by diurnal regulation, see ref. 17 , and this implies that the AtMYBD transcription factor may function to control downstream processes in a circadian clock-dependent manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genes involved in the glycosylation of flavonols—essential for enhancing their solubility in water and accumulation in plant cells 68 —namely VviGT5 (VIT_11s0052g01630) and VviGT6 (VIT_11s0052g01600), were connected with VviHYH within one and two steps, respectively. An Arabidopsis MYB-like domain TF homolog ( VviMYBD , VIT_01s0026g01050), involved in the regulation of anthocyanin biosynthesis, 69 was also co-regulated with VviHYH ( k  =   2). These observations reaffirm the involvement of VviHYH submodule genes in light-regulated transcriptional and secondary metabolism networks in a stress-related context.…”
Section: Resultsmentioning
confidence: 99%
“…Its Arabidopsis homolog (AtMYB113) is an activator of the anthocyanin pathway. Recently, AtMYBD was shown to enhance anthocyanin biosynthesis by repressing the negative regulator MYBL2 (Nguyen et al, 2015). The expression of an AtMYBD homolog (c28480.graph_c0) was upregulated in late ripening stages, but it does not show significant correlation with any structural genes.…”
Section: Discussionmentioning
confidence: 99%